Adequação do ensino da arquitetura à ética ambientalista: análise da dimensão ecológica no ensino acadêmico de projeto de arquitetura em Curitiba - Beatrice, Claudionor (2007)
Architecture and urbanism are facing rapid changes, and are urged to adapt to the challenges of environmental sustainability, which requires the adoption of an “environmental ethics”, observing economical, social and environmental constraints. The importance of the architect in this process arises from her/his academic background and the breadth of the professional activity, involving several fields of human activity, and creating functional, symbolic and spatial relationships with future generations. Architecture, specially in the second half of the XX century, grew apart from nature, favoring aesthetic and symbolic expressions in detriment of more elementary organic aspects of construction. Economic, social, and environmental aspects of this trend might compromise future generations, if counter-actions, already taking place in a few societies, are not taken immediately. The present study highlights the importance of the role played by educators in the establishment of criteria for design choices which might favor environmental sustainability through architecture. The work also compares some environmental actions implemented in other societies, and observes the birth of a new form of plastic-constructivist expression. Mainly, the work looks at the recent history of Architecture and Urbanism academic programs in Curitiba, examining the pro-environmental changes introduced in course syllabi and curricula